Political challenges and crisis management in the Islamic Republic of Iran: a comprehensive analysis - Ebrahim Abbasi (Discover Global Society)
Abstract The Islamic Republic of Iran, since its inception, has faced numerous internal and external challenges that have shaped its political, economic, and social landscape. This article examines the key issues affecting the country, including the regime's political legitimacy, the role of the Islamic Revolutionary Guard Corps (IRGC) in both domestic and foreign affairs, and the ongoing tensions with the West, particularly the United States and Israel. Furthermore, the article addresses the significant economic challenges, such as corruption, mismanagement, and the impacts of international sanctions, which have intensified the social unrest in the country. Through a thorough analysis of these factors, the paper provides insights into the structural and strategic aspects of the regime's actions. It explores how the Islamic Republic's foreign policy, particularly its stance towards Israel and its alliances with Russia and China, has influenced both regional and global relations. Additionally, the article looks at the internal dynamics, especially the growing dissatisfaction among the people, which has led to increasing calls for reform. The study concludes that Iran's political and economic trajectory depends on its ability to adapt to both internal and external pressures. The article highlights the critical need for substantial reforms in governance and foreign policy to address the root causes of the country's crises. Despite the regime's defensive and often repressive measures, the potential for significant change remains, contingent upon whether the leadership can respond effectively to the demands of the people and the international community. This study uniquely combines insider perspectives with quantitative economic data to provide a multidimensional understanding of Iran’s regime dynamics, offering new insights into the interplay between internal repression and external policy strategies.